Effect of Specimen Dimensions on Investigation of Modulus of Rigidity in Torsion Testing - Patil, Rajkumar D.; Gore, Purushottam N. (Asian Journal of Engineering and Applied Technology, 2015)
In the present paper, the effect of different specimen dimensions on the modulus of rigidity of mild steel (AISI 1020) in torsion testing is investigated. The experiments were conducted with dimension variables such as total length, useful length, outer diameter and fillet radius at different levels. For every combination of dimension variables, modulus of rigidity was found. To obtain optimum value of modulus of rigidity, the experimental data was used and effect of varying levels of each variables on the modulus of rigidity was investigated. The Taguchi parameter design and optimization approach is used. Percentage contribution of each dimension variable to decide modulus of rigidity is also calculated by ANOVA approach.